2011
DOI: 10.1038/aps.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral and genotoxic parameters of antipsychotic agent aripiprazole in mice

Abstract: Aim: Aripiprazole is an antipsychotic agent to treat schizophrenia, which acts through dopamine D 2 partial agonism, serotonin 5-HT 1A partial agonism and 5-HT 2A antagonism. This study was designed to evaluate the neurobehavioral effects and genotoxic/mutagenic activities of the agent, as well as its effects on lipoperoxidation. Methods: Open field and inhibitory avoidance tasks were used. Thirty min before performing the behavioral tasks, adult male CF-1 mice were administered aripiprazole (1, 3 or 10 mg/kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…While some studies observed improved spatial learning abilities [95,93], other studies failed to show significant treatment effects [105]. Similar observations were made using non-spatial learning paradigms; while aripiprazole reversed learning deficits in some trials [85,106,107], it failed to do so in another study [108].…”
Section: Learning and Memorysupporting
confidence: 52%
“…While some studies observed improved spatial learning abilities [95,93], other studies failed to show significant treatment effects [105]. Similar observations were made using non-spatial learning paradigms; while aripiprazole reversed learning deficits in some trials [85,106,107], it failed to do so in another study [108].…”
Section: Learning and Memorysupporting
confidence: 52%
“…Atypical antipsychotics such as olanzapine, risperidon and quetiapine did not induce genotoxicity in human whole blood cultures (Togar et al, 2012) and prevented DNA fragmentation (Qing et al, 2003). Contrary to these studies, there are studies in literature reporting that perphenazine (Gil-ad et al, 2001) valproic acid and ziprasidone (Karapidaki et al, 2011) and aripiprazole (Picada et al, 2011) leads to DNA damage. It is argued that typical antipsychotics are more toxic than atypical ones (Gil-ad et al, 2001;Parikh et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, some studies have focused on the some beneficial effects of antipsychotic drugs in brain diseases, including schizophrenia (He et al, ; Picada et al, ; Castellano et al, ). The chronic administration of RIS reverses locomotor hyperactivity in a rat model of schizophrenia (Castellano et al, ).…”
mentioning
confidence: 99%